Systems approach to livestock development oriented research: ILCA's experience - Rey, B.; Fitzhugh, H.K. (1994)
From its establishment in 1974, the International Livestock Center for Africa (ILCA) has followed a systems approach. Research planning and implementation incorporates description of systems, diagnosis of constraints, development and evaluation of interventions, and transfer of appropriate technologies. Models at various types are used for exante by systems analysis, and for organizing and analyzing data generated from systems research. Initial ILCA systems research concentrated on description of major African livestock production systems, including pastoral, transhumant, and agropastoral systems in Mali, Kenya, Ethiopia and Nigeria. These systems studies have involved interdisciplinary teams which addressed both agroecological and socioeconomic elements of the target production systems. These studies have contributed substantially to understanding the major constraints and interacting systems processes. Interventions developed and evaluated have included the oxen drawn broad bed maker for Vertisols in Ethiopian highlands, multipurpose trees for alley farming for smallholders in humid/subhumid zone, legumes in fodder banks for supplementing cattle and small ruminants in agropastoral systems, inter alia. Methodological lessons and perspectives are drawn from these experiences.